2019
DOI: 10.1590/2447-536x.v25i3.2057
|View full text |Cite
|
Sign up to set email alerts
|

Increased assimilates in lily yearling bulblets by fertilizer supplement of magnetic nano-composite

Abstract: In bulb production period, the promotion of photosynthesis and, consequently, increased synthesis of carbohydrates have the particular importance to enhance the size and quality of the bulbs. The aim of this study was to investigate the effects of chitosan and magnetism on the synthesis of photosynthetic compounds. Magnetic nano-composite (MN) and carboxymethyl chitosan (CM) during the production period of yearling bulblet were used as experimental materials. The results showed that MN (15 mg L-1) had the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
(21 reference statements)
2
2
0
Order By: Relevance
“…Generally, application of HA was superior in its effect than CHT one, especially at highest concentration (2000 ppm) since giving the highest values for tested traits in both seasons. These results in accordance with findings of earlier studies which reported that application of CHT caused increase in total chlorophylls (Dzung et al, 2011;Salachna et al, 2015;Byczyńska, 2018;El-Khateeb et al, 2018 ), carbohydrates content (Bistgani et al, 2017;Shafiei-Masouleh, 2019) and K, Ca% (Dzung et al, 2011). Whereas, the marked increase in tested components due to HA treatments are in conformity with prior studies that reported stimulatory influence of HA in augmentation of chlorophylls and carbohydrates content (Farahat et al, 2012;El Sayed et al, 2016;Abou Dahab et al, 2017;Noor El-Deen and El-Ashwah, 2019), increase K% (Zhang et al, 2014;Ibrahim et al, 2016;Noroozisharaf and Kaviani, 2018) and Ca% (Nikbakht et al, 2008;Dorria et al, 2018).…”
Section: Chemical Constituents Chlorophylls Content and Total Carbohysupporting
confidence: 92%
“…Generally, application of HA was superior in its effect than CHT one, especially at highest concentration (2000 ppm) since giving the highest values for tested traits in both seasons. These results in accordance with findings of earlier studies which reported that application of CHT caused increase in total chlorophylls (Dzung et al, 2011;Salachna et al, 2015;Byczyńska, 2018;El-Khateeb et al, 2018 ), carbohydrates content (Bistgani et al, 2017;Shafiei-Masouleh, 2019) and K, Ca% (Dzung et al, 2011). Whereas, the marked increase in tested components due to HA treatments are in conformity with prior studies that reported stimulatory influence of HA in augmentation of chlorophylls and carbohydrates content (Farahat et al, 2012;El Sayed et al, 2016;Abou Dahab et al, 2017;Noor El-Deen and El-Ashwah, 2019), increase K% (Zhang et al, 2014;Ibrahim et al, 2016;Noroozisharaf and Kaviani, 2018) and Ca% (Nikbakht et al, 2008;Dorria et al, 2018).…”
Section: Chemical Constituents Chlorophylls Content and Total Carbohysupporting
confidence: 92%
“…The low est value (15.99 %) was obtained from plants irrigat ed with the longest intervals (12 days) and not received any biostimulators treatments, whereas the highest mean value (38.64%) was resulted from plants irrigated with the shortest intervals (3 days) and sprayed with BRs at 200 ppm. The results of increasing total carbohydrates due to CHT treatments are the same as the results of previous researches (Zohreh et al, 2017;ShafieiMasouleh, 2019;Elansary et al, 2020;Ashour et al, 2021;Salachna and Pietrak, 2021). While, the beneficial increase in total carbohydrates due to BRs treatments are in agreement with earlier studies (Mohamed, 2020;Pacholczak et al, 2021).…”
Section: Total Carbohydrates (% Of Dry Matter)supporting
confidence: 91%
“…Chitosan (CHT) is a deacetylated derivative of chitin. It is a natural polymer and biodegraded by bio logical agents and it is environmentfriendly used in agriculture (ShafieiMasouleh, 2019). Under stressed conditions, CHT has the efficiency to mitigate the harmful effects of drought by promoting chlorophyll, carbohydrates, proline content and the capacity of antioxidant activities (Pirbalouti et al, 2017;Vosoughi, et al, 2018;Elansary et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, iron as the determinant element plays a role in other key biochemical processes, including respiration, symbiotic nitrogen fixation, electron transport system, biosynthesis of chlorophyll and cytochrome, nutrient uptake, and DNA and protein synthesis as well as photosynthesis as an activator. Alkaline soils may cause iron deficiency in many plant species (Nemati Lafmejani et al 2018 ; Hatamzadeh and Shafiei-Masouleh 2019a souleh 2019 ; Shafiei-Masouleh 2019 ; Haydar et al 2022 ). Iron is a low-mobile and more important micronutrient than other micronutrients for plants.…”
Section: Introductionmentioning
confidence: 99%